Metanephric adenoma with osseous metaplasia and bone marrow elements - Alessandro Pietro Aldera, MBChB; Jeff John, MBChB; Dharshnee Chetty, MBBCh FCPath; Dhirendra Govender, MBChB FRCPath PhD (Elsevier, 2019)
Metanephric adenoma is an uncommon benign renal neoplasm which typically occurs in the adult population. Although calcification is a common finding, osseous metaplasia is uncommon and may cause diagnostic difficulty on preoperative radiological imaging. Bone marrow elements (i.e. haematopoietic cells and adipose tissue) have been described in renal cell carcinomas but to our knowledge not in metanephric adenoma. We present a case of a 75-year-old woman diagnosed with a metanephric adenoma with the unusual finding of associated bone and bone marrow elements. To our knowledge, this is the first case report of bone marrow elements seen in association with metanephric adenoma. Keywords: Metanephric adenoma, Bone, Bone marrow, Osseous metaplasia, Extramedullary haematopoiesis, Kidney